Multi-Physics and Multi-Objective Design of an Axial Flux Permanent Magnet-Assisted Synchronous Reluctance Motor for Use in Electric Vehicles - Emre Gözüaçık; Mehmet Akar (Machines, 2025)
In this study, an axial flux double airgap permanent magnet-assisted synchronous reluctance motor (AF-Pma-SynRM) was designed for electric vehicles (EVs). The AF-Pma-SynRM model employs a forced liquid cooling method (cooling jacket) for a high current density. The model was tested using multi-objective optimization and multi-physics analysis. The AF-Pma-SynRM design has achieved 95.6 Nm of torque, 30 kW of power, and 93.8% efficiency at a 3000 rpm rated speed. The motor exhibits a maximum speed of 10,000 rpm, 253.1 Nm of torque, and 65 kW of output power. This study employs a novel barrier structure for axial motors characterized by fixed outer and inner dimensions, and is suitable for mass production. In the final stage, the motor was cooled using the cooling jacket method, and the average temperature of the winding was measured as 73.83 °C, and the average magnet temperature was 66.44 °C at a nominal power of 30 kW. Also to show variable speed performance, an efficiency map of the AF-Pma-SynRM is presented.